Structure-Based Design of Ricin Inhibitors - Jon D. Robertus; Eric V. Anslyn; Jeffrey Pruet; Karl Jasheway (Toxins, 2011)
Ricin is a potent cytotoxin easily purified in large quantities. It presents a significant public health concern due to its potential use as a bioterrorism agent. For this reason, extensive efforts have been underway to develop antidotes against this deadly poison. The catalytic A subunit of the heterodimeric toxin has been biochemically and structurally well characterized, and is an attractive target for structure-based drug design. Aided by computer docking simulations, several ricin toxin A chain (RTA) inhibitors have been identified; the most promising leads belonging to the pterin family. Development of these lead compounds into potent drug candidates is a challenging prospect for numerous reasons, including poor solubility of pterins, the large and highly polar secondary binding pocket of RTA, as well as the enzyme’s near perfect catalytic efficiency and tight binding affinity for its natural substrate, the eukaryotic ribosome. To date, the most potent RTA inhibitors developed using this approach are only modest inhibitors with apparent IC50 values in the 10−4 M range, leaving significant room for improvement. This review highlights the variety of techniques routinely employed in structure-based drug design projects, as well as the challenges faced in the design of RTA inhibitors.